«Журнал путешествия из Москвы в Нижний 1813 года» князя И. М. Долгорукова как один из первых внутренних травелогов в русской классической литературе - Никольский, Евгений; Nikolsky, Eugene (Східноєвропейський національний університет імені Лесі Українки, 2015)
В статье анализируется неизвестный широко литературный и историко-культурный документ «Журнал путешествия из Москвы в Нижний 1813 года», составленный князем И. М. Долгоруким (1764-1823); произведение рассматривается с точки зрения его жанрово специфики, именно как травелог в контексте развития данного жанра в русской литературе и с позиции его социально-тематической специфики, отмечается критический взгляд автор на некоторые общественные явления, отмечается лирические моменты: любовь к Нижегородской земле, искренняя религиозность, преклонение пред благочестием, любование природой. Рассматривается рецепция автором быта и нравов эпохи, отмечается его демократический, чуждый кастовых предрассудков подход к восприятию социальных реалий. "Journal of a journey from Moscow to Nizhny 1813" by Prince Ivan Mikhailovich Dolgorukov as a document of the Alexander era. The article analyzes the widely unknown literary, historical and cultural document "Journal of a journey from Moscow to Nizhny 1813", composed by Prince I. M. Dolgoruky (1764¬1823); the work is considered from the standpoint of its genre specific, it is like a travelogue in the context of the development of this genre in Russian literature and its socio-thematic specificity, notes critical view of the author on some social phenomenon, celebrated lyrical moments: the love of the Nizhniy Novgorod earth, sincere religiosity, to bow before the piety, admiration of nature. Discusses the reception of the author of the life and mores of the era, noting that it is democratic, alien caste prejudice approach to the perception of social realities. In the final scientific presentation of the material coexist with asiaticism, concludes, what feelings awakens the visit to Nizhny Novgorod in the nineteenth and twenty-first centuries. In the scientific revolution introduced early unknown material.
"Travel Journal from Moscow To Nizhny 1813" by Prince I. M. Dolgorukov as One of the First Inside Travelogues in Russian Classical Literatur
Keywords: травелог; литература путешествий; travelogue; travel literature